Analisis Rasio Likuiditas, Solvabilitas, Aktivitas, Pertumbuhan Dan Profitabilitas Terhadap Earning Per Share Terhadap PT. Bank BRI Tbk Pada Tahun 2018-2021 - Riondi Solomon Zugia Sihombing; Dhuti Widhiyas Tutik; Natalie Natalie; Thomas Firdaus Hutahaean; Saut Maruli Tua Pandiangan (Journal of Economic, Bussines and Accounting (COSTING), 2024)
Reviewing a bank's financial statements, which consist of an income statement and balance sheet, and applying ratio analysis techniques can help someone assess a bank's financial performance. Ratios are measures used to assess the financial records of a business, including non-banking and banking companies. The aim of this research is to examine the effect of profitability, solvency and liquidity ratios on earnings per share of PT Bank Rakyat Indonesia Tbk. The approach used is quantitative. The Indonesian Stock Exchange, papers, journals, academic publications, and certain media records are some of the data sources used in this research. We need information on the dividend policy received by the BRI company between 2018 and 2021. F test, T test, R-squared test, and multiple linear regression analysis are examples of data analysis techniques. The strong beneficial influence of the ROA variable on EPS at Bank Rakyat Indonesia is shown by partial data. At Bank Rakyat Indonesia there is no significant and positive correlation between the CR and EPS variables. At Bank Rakyat Indonesia, the ACT variable has a significant and partially beneficial influence on EPS. At Bank Rakyat Indonesia, the DER variable has a significant and beneficial influence on EPS.